Management of Intellectual Property as a Generator of Resources in Mexican Higher Education Institutions - Rodríguez, Fernando; Vivanco Vargas, Martin; Gómez Salazar, Moisés (Mercados y Negocios, 2024)
This paper was developed to analyze the level of implementation of intellectual property management processes in Higher Education Institutions (HEI). Intellectual Property management processes in the public sector have been reduced, at least in understanding the concept, to the processes of protecting and maintaining intellectual property titles; however, it is a more extensive process than conceptualized. In this sense, Martinez et al. (2018) generated a methodology involving 19 indicators (processes) of intellectual property management implemented during the R&D&I process. These indicators were used to measure their implementation in Mexican public sector HEIs with information from the transparency portal. The research shows the importance of generating multidisciplinary groups in R&D&I processes, enhancing the financial redundancy of research investment.